Synthesis of nanocrystalline rutile - Samuel, V; Pasricha, R; Ravi, V (Ceramics International, 2005)
Nanocrystalline titanium dioxide (TiO2) in the rutile phase has been obtained by homogeneous precipitation using urea and TiOCl2. A mixture of urea and TiOCl2 is heated on a hot water bath at 65-75 degrees C to precipitate rutile powders. X-ray diffraction (XRD) studies on these oven-dried powders indicated the formation of single-phase rutile. Raman scattering experiments were also performed to confirm the formation of the rutile phase. Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 40 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; Electron microscopy; powders; TiO2; X-ray methods

Synthesis of Sr0.5Ba0.5Nb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Chemistry and Physics, 2005)
A gel was formed when an aqueous solution of BaCl2, SrCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I kHz is 1000. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-Tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides